Characterization and numerical simulation of liquid refrigerant R-134a flow emerging from a flooded evaporator tube bundle - Asher, William E.; Eckels, Steven J. (My University, 2019)
The distribution of liquid droplets emerging from an evaporator tube bundle is characterized for refrigerant R-134a with a triangular tube arrangement with a pitch of 1.167. The purpose of this research was to improve understanding of the droplet ejection process to aid in design of evaporators typically used in larger chiller systems. A laser and camera system captured images of the evaporator headspace at varying conditions. Conventional shadowgraphy techniques were applied to recognize and match droplets for velocity calculations. The evaporator conditions varied with bundle mass fluxes of 20.3 and 40.7 kg s−1m−2, top-rows heat fluxes of 15.8 and 31.5 kWm−2, and outlet saturation temperatures of 4.4 and 12.8 °C. Conditions ranged from flooded to dryout of the top rows. Droplet number, size distribution, velocity, and liquid volume fraction are presented in the headspace above the bundle. A method to numerically duplicate the droplet loading in the headspace using CFD with a Lagrangian discrete-phase model is also presented and verified, providing a powerful design tool. Liquid distribution in the headspace is found to be a strong function of all varied properties, particularly mass flux, liquid level, and saturation temperature.
Citation: Asher, W. E., & Eckels, S. J. (2019). Characterization and numerical simulation of liquid refrigerant R-134a flow emerging from a flooded evaporator tube bundle. International Journal of Refrigeration, 107, 275–287. https://doi.org/10.1016/j.ijrefrig.2019.07.001